Enhanced Enzymatic Activity of Glycerol-3-Phosphate Dehydrogenase from the Cryophilic Saccharomyces kudriavzevii - Oliveira, Bruno M.; Barrio, Eladio; Querol, Amparo; Pérez-Torrado, Roberto (PLOS ONE, 2014)
During the evolution of the different species classified within the Saccharomyces genus, each one has adapted to live in different environments. One of the most important parameters that have influenced the evolution of Saccharomyces species is the temperature. Here we have focused on the study of the ability of certain species as Saccharomyces kudriavzevii to grow at low temperatures, in contrast to Saccharomyces cerevisiae. We observed that S. kudriavzevii strains isolated from several regions are able to synthesize higher amounts of glycerol, a molecule that has been shown to accumulate in response to freeze and cold stress. To explain this observation at the molecular level we studied the expression of glycerol biosynthetic pathway genes and we observed a higher expression of GPD1 gene in S. kudriavzevii compared to S. cerevisiae in micro-vinification conditions. We observed higher enzymatic activity of Gpd1p in S. kudriavzevii in response to osmotic and cold stress. Also, we determined that S. kudriavzevii Gpd1p enzyme presents increased catalytic properties that will contribute to increase glycerol production. Finally, we evaluated the glycerol production with S. cerevisiae, S. kudriavzevii or a recombinant Gpd1p variant in the same background and observed that the S. kudriavzevii enzyme produced increased glycerol levels at 12 or 28°C. This suggests that glycerol is increased in S. kudriavzevii mainly due to increased Vmax of the Gpd1p enzyme. All these differences indicate that S. kudriavzevii has changed the metabolism to promote the branch of the glycolytic pathway involved in glycerol production to adapt to low temperature environments and maintain the NAD+/NADH ratio in alcoholic fermentations. This knowledge is industrially relevant due to the potential use, for example, of S. cerevisiae-S. kudriavzevii hybrids in the wine industry where glycerol content is an important quality parameter.